Do trade partners’ labour standards affect ASEAN’s labour standards? - Said, Rusmawati; Ng, Kar Yee; Ismail, Normaz Wana (Faculty of Economics and Administration, University of Malaya, 2019)
This paper investigates the impact of foreign labour standards on domestic labour standards in ASEAN countries. The study employs a set of cross-sectional time series data that covers the period from 1995-2008 for its empirical analysis. Three different labour standards indicators, namely numbers of strikes and lockouts, cases of occupational injuries, and trade union density rates–are used as a proxy for labour standards. The results evince a race to the bottom for labour standards, represented by cases of injuries. In contrast, the effect of trade partners’ trade union density rate is negative and significant; however, the number of strikes and lockouts has an insignificant effect. The findings of the study suggest that there may be a race to the bottom in terms of working conditions among ASEAN countries, but not on the standards that measure the rights of workers.